Ales Adamavich Speaking at Newman Center - Watkins, Howard::::::::: (1988)
Ales Adamavich speaking from dais at Newman Center; seated John Romine, Craig Barnes, and George Bulow Flags of USSR and USA separated by Beyond War photograph of Earth